2018
DOI: 10.1186/s40068-018-0108-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-application of biochar and cattle manure counteract positive priming of carbon mineralization in a sandy soil

Abstract: Background: Application of biochar has been suggested as a carbon (C) management strategy to sequester C and enhance soil quality. An incubation study was carried out to investigate the interactive effect of biochar and cattle manure application on mineralization of carbon (C) in a tropical coastal savanna sandy soil. Methods: The soils were amended with three sole levels of cattle manure (0, 13 and 26 tons ha −1) or biochar (0, 20 and 40 tons ha −1) and four combined manure-biochar levels (20 or 40 tons ha −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The higher CWC, HWC, CWN, and HWN in soils amended with DMP compared with those of the sole amendment suggest a synergistic interaction between biochar and manure to form decomposable compounds that transformed into labile fractions. Similar findings were reported by Dodor et al () who observed an increased labile C in soils amended with the addition of manure–biochar mixture. The higher level of water‐soluble fractions with the DMP may be due to the addition of a higher amount of organic matter and microbial activity.…”
Section: Resultssupporting
confidence: 91%
“…The higher CWC, HWC, CWN, and HWN in soils amended with DMP compared with those of the sole amendment suggest a synergistic interaction between biochar and manure to form decomposable compounds that transformed into labile fractions. Similar findings were reported by Dodor et al () who observed an increased labile C in soils amended with the addition of manure–biochar mixture. The higher level of water‐soluble fractions with the DMP may be due to the addition of a higher amount of organic matter and microbial activity.…”
Section: Resultssupporting
confidence: 91%
“…The increased TN content with manure (0.36%), liquid humus (0.31%) and compost (0.31%) amendments were noted in the previous studies [36]. Moreover, there is a TN increase in biochar (1.6 g/kg) and cattle manure (11.6 g/kg) when treated sandy soil compared to control group (0.18 g/kg) [37]. But in the present finding the high TN content was observed in BAS.…”
Section: A Effects Of Oas On Soil Physicochemical Propertiessupporting
confidence: 55%
“…However, the combined effect of manure and the other soil amendment (e.g., biochar) has not been widely studied. In a few studies in which manure-derived biochar was applied to soils, a mostly positive effect was seen [33,34], but also a converse [34][35][36] effect on plant growth and soil microbial diversity was observed.…”
Section: Introductionmentioning
confidence: 99%